From neural chip and engineered biomolecules to bioelectronic devices: An overview - Nicolini, C. (Biosensors & bioelectronics, 1995)
At the first C.E.C. Workshop, in Brussels on 28–29 November 1991, attended by over 70 leading European scientists and industrialists, bioelectronics was defined as the ‘the use of biological materials and biological architectures for information processing systems and new devices’. At the end of the Frankfurt Workshop, bioelectronics, specifically bio-molecular electronics, was described as ‘the research and development of bio-inspired ( i.e. self-assembly) inorganic and organic materials and of bio-inspired ( i.e. massive parallelism) hardware architectures for the implementation of new information processing systems, sensors and actuators, and for molecular manufacturing down to the atomic scale’. The subject of this overview is to summarize some of the most significant progress in bio-molecular electronics from neural VLSI networks and bio-molecular engineering. As an example of one possible route, emphasis is placed on the results recently obtained within this laboratory.